(3Gdbhd GdeCfhS HTQM eZdb GdbGehSs - (3HOQ GdOjf GdbQGais; (3GdcQeGfj , CMeO Hf YHO Gddg, MejO GdOjf MLI GdYQGajf,J (B412 (3g` s ((3CMeO Hf NWGH GdefTGhi GdTYQGhi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Rjf ef CQGO GdJMdi HCTQa GddZGJ hHYO adG jNai Cf Yde GddZI ef CTQa GdYdhe hGdhbha Ydi ZhGeVI ef CLd GdeYdhe s
(3BNQgG (B:s
(3aWQH GdeHQO ef gPG GdLhGH MJi Tb KhHI GfJgi eG jJSQ LeYg ef GdahGFO GdTQjaI s
(3HChdg GdYOjO ef GdJedcGJs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B156 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B297s
Keywords: (3eJaQbGJs